The COMT Val158Met Polymorphism and Reaction to a Transgression: Findings of Genetic Associations in Both Chinese and German Samples - Sindermann, Cornelia; Luo, Ruixue; Zhang, Yingying; Kendrick, Keith M.; Becker, Benjamin; Montag, Christian (Frontiers in Behavioral Neuroscience, 2018)
After a transgression, people often either tend to avoid the transgressor or seek revenge. These tendencies can be investigated via a trait approach and surprisingly little is known about their biological underpinnings. One promising candidate gene polymorphism, which may influence individual differences in avoidance of a transgressor and vengefulness, is the COMT Val158Met (rs4680) polymorphism known to affect dopaminergic signaling and among others brain activity in situations in which people punish others for their behavior. We therefore investigated the molecular genetics of individual differences in Avoidance Motivation and vengefulness with a focus on this polymorphism. Possible genetic associations were first investigated in a sample of N=730 Chinese participants (n=196 females) using buccal cells to extract the DNA for genotyping. To replicate the findings we carried out a parallelized investigation in a sample of N=585 German participants (n=399 females). Chinese and German versions of the TRIM-12 and the Vengeance Scale were implemented to assess individual differences in tendencies to react to a transgression. Results show that Met allele carriers of the COMT Val158Met polymorphism (Val/Met and Met/Met) score significantly higher on the tendency to avoid a transgressor in the Chinese male and female samples, with an especially pronounced effect in the female subgroup. The same effect could be found in the German sample, again especially in females. Additionally, carrying a Met allele was associated with higher vengefulness in the Chinese sample only, especially in males. The present findings indicate that the COMT Val158Met polymorphism might influence individual differences in the motivation to avoid transgressors across cultures, especially in females. However, its association with vengefulness seems to be more complex and may exhibit some cultural and gender specific effects.